2022
DOI: 10.1007/s00262-022-03323-0
|View full text |Cite
|
Sign up to set email alerts
|

TCF-1 regulates NKG2D expression on CD8 T cells during anti-tumor responses

Abstract: Cancer immunotherapy relies on improving T cell effector functions against malignancies, but despite the identification of several key transcription factors (TFs), the biological functions of these TFs are not entirely understood. We developed and utilized a novel, clinically relevant murine model to dissect the functional properties of crucial T cell transcription factors during anti-tumor responses. Our data showed that the loss of TCF-1 in CD8 T cells also leads to loss of key stimulatory molecules such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…In this study, we defined a TCF1 + PD-1 + progenitor population that could foster progeny cells producing effector molecules. Combined with the recent observation that TCF1 expression in CD8 + T cells is essential in the pathogenesis of acute GvHD 46 , this provides promising insight into opportunities for the development of therapeutics for acute GvHD. Eliminating the progenitor population or inhibiting the differentiation of the progenitor subset could be useful in mitigating acute GvHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we defined a TCF1 + PD-1 + progenitor population that could foster progeny cells producing effector molecules. Combined with the recent observation that TCF1 expression in CD8 + T cells is essential in the pathogenesis of acute GvHD 46 , this provides promising insight into opportunities for the development of therapeutics for acute GvHD. Eliminating the progenitor population or inhibiting the differentiation of the progenitor subset could be useful in mitigating acute GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results in chronic viral infection and cancer 12 20 , TCF1 + progenitor CD8 + T cells possessed exclusive proliferative potential, were able to differentiate into TCF1 - progeny CD8 + T cells harboring effector molecules via antigenic stimulation, and predominantly localized to the spleen. In addition to the recent discovery of the TCF1 + CD8 + T cell subset in the models of GvHD and Graft-versus-leukemia (GvL) 44 , 45 , Harris et al demonstrated that the loss of TCF1 in donor CD8 + T cells reduced the severity and persistence of GvHD symptoms in the MHC-mismatched GvHD model 46 . These findings suggest that the generation of the TCF1 + progenitor CD8 + T cell subset represents a common mechanism of CD8 + T cell differentiation, which plays a crucial role in sustaining antigen-specific CD8 + T cells in microenvironments with persistent antigenic stimulation, such as allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%